Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcimb.2022.780354
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis in Ocular Mucous Membrane Pemphigoid

Abstract: Mucous Membrane Pemphigoid is an orphan multi-system autoimmune scarring disease involving mucosal sites, including the ocular surface (OcMMP) and gut. Loss of tolerance to epithelial basement membrane proteins and generation of autoreactive T cell and/or autoantibodies are central to the disease process. The gut microbiome plays a critical role in the development of the immune system. Alteration in the gut microbiome (gut dysbiosis) affects the generation of autoreactive T cells and B cell autoantibody repert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Previous studies have reported that some butyrate-producing bacteria of Coprococcus spp. ( Firmicutes ) could stimulate aberrant hyperproliferation of colonic epithelial cells with MSH2 or MLH1 deficiency and enhance β-catenin activity by increasing butyrate levels ( 50 52 ). Dronamraju et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that some butyrate-producing bacteria of Coprococcus spp. ( Firmicutes ) could stimulate aberrant hyperproliferation of colonic epithelial cells with MSH2 or MLH1 deficiency and enhance β-catenin activity by increasing butyrate levels ( 50 52 ). Dronamraju et al.…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, other autoimmune bullous diseases such as mucous membrane pemphigoid (MMP) have been investigated and GM dysbiosis was observed in MMP patients. 14 In BP patients, the skin microbiota composition has been proven to be substantially different from the healthy people and a novel indicator of disease. 15 The GM in BP patients has rarely been examined.…”
Section: Introductionmentioning
confidence: 99%
“…16 Immunosuppressive agents can change the composition of GM and reduce the diversity, leading to an imbalance of GM and further aggravating the disease in MMP patients. 14 Although these studies identified that changes in the GM were associated with treatment, little is known about the variations during BP treatment. Investigation into the different stages of BP may help us understand the mechanism of treatment better.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations